3D printing high-thermal-conductivity precursor converted silicon carbide ceramic as well as preparation method and application thereof

By combining 3D printing with precursor conversion and multiple impregnation sintering, the problems of traditional silicon carbide ceramics being difficult to form into complex shapes and having insufficient performance have been solved, and silicon carbide ceramics with high density and high thermal conductivity have been prepared, which are suitable for aerospace and electronics fields.

CN121085642APending Publication Date: 2025-12-09SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511267800.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Traditional silicon carbide ceramic manufacturing methods are difficult to form complex shapes, and silicon carbide ceramics prepared by 3D printing have large shrinkage rates, loose structures, and lower mechanical and thermal properties than dense silicon carbide ceramics prepared by traditional sintering methods, which limits their application range.

Method used

By combining 3D printing technology with precursor conversion, silicon carbide powder, modified B4C nanoparticles, and polycarbosilane powder are stirred evenly in an aromatic or chlorinated hydrocarbon organic solvent and then ball-milled to prepare a slurry. The slurry is then impregnated in a vacuum impregnation solution and sintered at high temperature. High-density silicon carbide ceramics are generated by repeatedly impregnating and sintering β-SiC powder with phenolic resin and modified nano-Si powder.

Benefits of technology

It enables efficient molding of complex-shaped silicon carbide ceramics, significantly improving the density and thermal conductivity of the ceramics, and enhancing their mechanical strength. It is suitable for high-temperature components in aerospace and heat dissipation/packaging of electronic and power semiconductors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121085642A_ABST
    Figure CN121085642A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic non-metallic materials, and discloses a 3D printing high-thermal-conductivity precursor converted silicon carbide ceramic and a preparation method and application thereof.The preparation method comprises the following steps that silicon carbide powder, modified B4C nano powder and polycarbosilane powder are added into excessive aromatic hydrocarbon or / and chlorinated hydrocarbon organic solvents according to the proportion, stirring is conducted, and a mixture is obtained; uniformly stirring in an inert atmosphere, putting into a planetary ball mill, carrying out ball milling, setting the rotating speed time, and uniformly mixing the raw materials to obtain slurry; after the solid content of the slurry is adjusted to a set value, a ceramic green body is prepared through 3D printing, the green body is dried and sintered, and a precursor converted silicon carbide ceramic part is prepared; the preparation method comprises the following steps: adding silane coupling agent modified nano Si powder, beta-SiC powder and phenolic resin into ethanol according to a ratio, and uniformly mixing to obtain an impregnation liquid; and carrying out vacuum impregnation on the precursor-converted silicon carbide ceramic piece in the impregnation liquid, and after impregnation is completed, carrying out curing and sintering so as to obtain the silicon carbide ceramic with high mechanical strength and good heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of inorganic non-metallic materials, and more particularly relates to a 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic and a preparation method and application thereof. BACKGROUND

[0002] The statements herein are provided only to enhance understanding of the present application and are not necessarily intended to constitute the prior art.

[0003] Silicon carbide ceramics have important application value in high-temperature structural parts due to their excellent mechanical properties (especially high bending strength at high temperatures above 1000℃) and good thermal conductivity (helping to quickly conduct accumulated heat and reduce the risk of local overheating of devices). However, traditional silicon carbide ceramic manufacturing methods (such as dry pressing and slip casting) usually have the problems of complex process, high sintering temperature and difficulty in forming complex-shaped components, which are difficult to meet the needs of special-shaped and complex-structured silicon carbide ceramic parts in the current technological development.

[0004] 3D printing technology, as a mold-free integrated forming technology, has shown significant advantages in ceramic preparation. The precursor conversion method for preparing silicon carbide ceramics has the advantages of low sintering temperature and precise control of the microstructure of the ceramic, which helps to optimize the material properties. However, the ceramic prepared by this method usually has the disadvantages of large shrinkage and relatively loose structure, which leads to its mechanical properties (such as strength) and thermal conductivity being lower than those of the dense silicon carbide ceramic prepared by traditional sintering method, limiting its application range. SUMMARY

[0005] In view of the deficiencies of the prior art, the present application aims to provide a 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic and a preparation method and application thereof, which can prepare complex-shaped and high-performance silicon carbide ceramic materials.

[0006] To achieve the above-mentioned purpose, the present application is realized by the following technical solutions: In a first aspect, the present application provides a preparation method of a 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic, comprising the following steps: The silicon carbide powder, modified B4C nano-powder and polycarbosilane powder are added into an excess of aromatic hydrocarbon or / and chlorinated hydrocarbon organic solvent in a proportion, stirred uniformly under inert atmosphere, and then put into a planetary ball mill for ball milling, with the rotation speed and time being set to mix the raw materials uniformly to obtain a slurry; after adjusting the solid content of the slurry to a set value, a ceramic green body is prepared by 3D printing, and the green body is dried and sintered to obtain a precursor-converted silicon carbide ceramic part; The nano-Si powder modified with a silane coupling agent, β-SiC powder and phenolic resin are added into ethanol in a proportion, mixed uniformly to obtain an impregnating solution; Vacuum-impregnate the precursor-transformed silicon carbide ceramic piece in the impregnation solution for 1-6 hours, and after impregnation, solidify first, and then sinter at 1000-1700 DEG C, to obtain the 3D-printed high-thermal-conductivity precursor-transformed silicon carbide ceramic.

[0007] In a second aspect, the present application provides a 3D-printed high-thermal-conductivity precursor-transformed silicon carbide ceramic, which is prepared by the preparation method.

[0008] In a third aspect, the present application provides an application of the 3D-printed high-thermal-conductivity precursor-transformed silicon carbide ceramic in the field of aerospace high-temperature components or electronic and power semiconductor heat dissipation / packaging.

[0009] The beneficial effects achieved by one or more embodiments of the present application are as follows: Compared with the traditional silicon carbide ceramic preparation process, the extrusion type 3D printing technology does not need to prepare a mold in advance and can be integrated into complex structures, greatly shortening the process cycle and saving economic costs.

[0010] The addition of silicon carbide powder in the precursor solution reduces the shrinkage rate of the ceramic piece during the precursor transformation and sintering process, improves the density of the ceramic, and the modified B4C nano powder can effectively refine the grains and heal the micropores to improve the thermal conductivity.

[0011] The precursor-transformed silicon carbide ceramic is impregnated and sintered multiple times using a phenolic resin, modified nano Si powder and β-SiC powder solution, the pores in the precursor-transformed ceramic are filled with carbon, and then the reaction sintering method is used to react with molten silicon to form silicon carbide, and nano Si powder and β-SiC can provide heterogeneous nucleation centers to refine the grains and reduce the shrinkage stress; a silicon carbide ceramic with high mechanical strength and good thermal conductivity is obtained. BRIEF DESCRIPTION OF DRAWINGS

[0012] The drawings accompanying the specification of the present application serve to provide a further understanding of the present application, and the illustrative embodiments of the present application and their descriptions serve to explain the present application and do not constitute an improper limitation on the present application.

[0013] Figure 1 It is an extrusion type 3D printing slurry extrusion line forming effect diagram in embodiment 1 of the present application, wherein a is a photo during extrusion; b is a photo of the slurry extrusion line; Figure 2 It is a thermal conductivity and bending strength numerical value trend chart of 3D-printed silicon carbide ceramic with different impregnation times in embodiment 1 of the present application; Figure 3 It is a 3D-printed silicon carbide ceramic cross-section SEM scanning diagram of printing impregnation 2 times (a) and impregnation 4 times (b) in embodiment 1 of the present application; Figure 4SEM images of the cross-section of the 3D printed SiC ceramic after etching Si for 2 times (a) and 4 times (b) in Example 3 of the present application. DETAILED DESCRIPTION

[0014] It should be noted that the following detailed description is illustrative only, and is intended to provide further description in order to provide a further understanding of the application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0015] In a first aspect, the present application provides a method for preparing a 3D printed high-thermal-conductivity precursor-transformed silicon carbide ceramic, comprising the following steps: The silicon carbide powder, modified B4C nanopowder and polycarbosilane powder are added to an excess of an aromatic hydrocarbon or / and chlorinated hydrocarbon organic solvent in a proportion, and then stirred uniformly under an inert atmosphere. The slurry is obtained by placing the mixture in a planetary ball mill and setting the rotation speed and time to mix the raw materials uniformly. After adjusting the solid content of the slurry to a set value, a ceramic green body is prepared by 3D printing. The green body is dried and sintered to obtain a precursor-transformed silicon carbide ceramic part. The silane coupling agent modified nano-Si powder, β-SiC powder and phenolic resin are added to ethanol in a proportion, and then mixed uniformly to obtain an impregnation solution. The precursor-transformed silicon carbide ceramic part is vacuum-impregnated in the impregnation solution for 1-6 h. After impregnation, the part is first solidified and then sintered at 1000-1700 ℃ to obtain the final product.

[0016] Polycarbosilane (PCS) is a core precursor for preparing SiC ceramics, and its molecular chain is composed of a Si-C skeleton and organic side groups (such as methyl and phenyl). PCS is a solid wax-like polymer at room temperature, which needs to be dissolved into a liquid state to be uniformly mixed with SiC powder to form a printing slurry.

[0017] Aromatic hydrocarbons (such as toluene and xylene): the benzene ring structure can interact with the silicon-carbon skeleton or organic groups in the PCS molecule (such as van der Waals force and π-π stacking effect), which helps to dissolve or highly disperse PCS to form a uniform and stable solution or colloidal dispersion system.

[0018] Chlorinated hydrocarbon organic solvents have high polarity and strong solubility. The presence of chlorine atoms enhances the polarity of the solvent, which can better dissolve or disperse PCS, an organic polymer with certain polarity.

[0019] On the basis of good dissolution or dispersion of the solvent for PCS, the PCS solution / gel can effectively wrap and wet the SiC powder particles through stirring to form a uniform slurry.

[0020] Aromatic hydrocarbons (such as toluene, xylene) and chlorinated hydrocarbons (such as dichloromethane, chloroform) generally have moderate boiling points and volatilities, which do not cause the viscosity of the slurry to change dramatically or the components to be uneven during the stirring and mixing stage. In the printing process, moderate volatility helps the material filament to maintain its shape after extrusion (solvent evaporation causes the slurry to be preliminarily solidified), but does not cause the nozzle to be blocked due to rapid evaporation in the printing head. The solvent is relatively easy to remove by mild heating or vacuum during the drying step, preparing for subsequent sintering.

[0021] PCS belongs to a non-polar Si-C main chain polymer, which can only be fully swollen and molecularly dissolved by solvents that are also "non-polar or weakly polar". Aromatic hydrocarbons or / and chlorinated hydrocarbons can quickly dissolve PCS into a low-viscosity solution, thereby significantly reducing the overall viscosity of the slurry and increasing the solid content of the slurry. It can be completely volatilized at 60-150°C, and after sintering, a SiC ceramic with higher purity and higher thermal conductivity can be obtained.

[0022] Under an inert atmosphere (such as nitrogen, argon), these solvents are relatively stable and are not prone to oxidation or other side reactions, ensuring the safety of the slurry preparation process and the stability of the slurry components. PCS treatment under an inert atmosphere is also key to preventing its oxidation and crosslinking.

[0023] Avoid using solvents containing active hydrogen (O-H, N-H) such as water or alcohols. PCS molecules contain active groups such as Si-H bonds, which can react violently with water or alcohol (hydrolysis, alcoholysis), leading to the decomposition, crosslinking or gelation of PCS, which destroys its function as a precursor and binder, and prevents the formation of qualified slurry.

[0024] The SiC matrix prepared by 3D printing + precursor conversion (PCS cracking) has problems such as microcracks, pores and structural inhomogeneity (resulting from solvent evaporation, PCS cracking shrinkage and sintering process), which are the root cause of brittle fracture of the material. During the impregnation process, nano β-SiC powder enters the pores of the ceramic matrix, and after sintering, the nano particles are dispersed in the carbon matrix formed by the cracking of phenolic resin. When the microcracks expand to the nano particles, the fracture energy is significantly consumed, and the toughness is improved.

[0025] Nanoscale Si powder with ultra-high specific surface area and β-SiC particles form strong interfacial bonding with the matrix (modified by silane coupling agent), which can effectively transfer load and improve strength and modulus. Nano particles act as a rigid skeleton, reducing the shrinkage stress generated by the high-temperature cracking of phenolic resin and reducing the generation of new defects.

[0026] SiC is an excellent thermal conductor (theoretical thermal conductivity > 200 W / m·K), but the presence of porosity and impurity phases (such as free carbon, SiO2) in the precursor-converted matrix hinders heat transfer. Silane coupling agent modification ensures strong bonding of nanoparticles to the matrix, significantly reducing interfacial thermal resistance; dispersed nano-Si powder and β-SiC can fix the SiC grain boundary of the matrix, preventing excessive grain growth at high temperatures, and play a role in refining the grain, which can improve the mechanical properties, fracture toughness and hardness of the ceramic material. The rigid nanoparticles hinder the movement of dislocations and grain boundary sliding at high temperatures, significantly improving the long-term high-temperature stability of the material.

[0027] Phenolic resin as a liquid impregnation medium provides a carbon source for cracking; while nano-Si powder and β-SiC as active fillers, give it functionality. Pure resin impregnation will leave a porous carbon skeleton after cracking, with extremely poor mechanical properties. The addition of nano-Si powder and SiC forms a reinforced skeleton, maintaining structural integrity.

[0028] The huge specific surface area of nano-Si powder and β-SiC powder results in extremely high surface energy, and there is strong attraction (Van der Waals force) between particles, which easily agglomerates into large secondary particles. Unmodified nano-powder will quickly settle and clump in ethanol or phenolic resin solution, and cannot form a stable and uniform impregnation solution. Moreover, the agglomerated powder will block the micropores and cracks inside the precursor-converted silicon carbide ceramic part, hindering the deep penetration of the impregnation solution, and reducing the efficiency and uniformity of impregnation.

[0029] The surface of unmodified nano-Si powder and β-SiC powder is usually hydrophilic / polar (with -OH groups, etc.), while phenolic resin (especially after curing) is relatively hydrophobic / non-polar. This difference in properties leads to poor interfacial compatibility between the two. During the subsequent curing and sintering process (accompanied by volume shrinkage and stress generation), as well as during the service process of the material, when subjected to load or thermal shock, this weak interface is prone to become a source of crack initiation and propagation, leading to premature failure of the material.

[0030] Silane coupling agent is wrapped around the surface of nano-Si powder and β-SiC powder, forming a layer of organic molecules. This layer of organic molecules reduces the surface energy of the nanoparticles, effectively reducing the strong Van der Waals force between nanoparticles, thereby significantly inhibiting the agglomeration of nano-powder. This allows the nano-powder to be uniformly and stably dispersed in ethanol solvent and the subsequent phenolic resin matrix, forming a homogeneous impregnation solution, ensuring consistent impregnation effect each time.

[0031] Well-dispersed nanoparticles can penetrate deep into the pores and micro-cracks of the ceramic green body with the impregnation solution, and the silane coupling agent establishes an effective connection between the nano-powder particles and the phenolic resin, helping to improve the interfacial bonding strength.

[0032] In some embodiments, the aromatic hydrocarbon-based organic solvent is toluene or xylene; and the chlorinated hydrocarbon-based organic solvent is chloroform or dichloromethane.

[0033] In some embodiments, the mass ratio of the polycarbosilane powder to the organic solvent is 1:1-5.

[0034] In some embodiments, the mass percentage of the silicon carbide powder in the slurry is 5-15%, and the mass percentage of the modified B4C nanopowder in the slurry is 0.5-3%.

[0035] In some embodiments, the planetary ball milling time is 0.5-2h to ensure uniform mixing of the silicon carbide powder, the modified B4C nanopowder and the polycarbosilane powder.

[0036] In some embodiments, the modified B4C nanopowder is prepared by adding a silane coupling agent to a mixed solution of xylene and water, adding the B4C nanopowder after uniform mixing, ultrasonicating for 30min, and then continuously stirring for 1-3h. After the reaction is completed, the product is washed with ethanol and dried.

[0037] Preferably, after the stirring is completed, the slurry is heated to evaporate the organic solvent in the slurry, and the solid content in the slurry is adjusted to 65-95%.

[0038] In some embodiments, the green body is dried by vacuum drying for 5-24h at a temperature less than 50℃ to reduce the impact of stress on the structure.

[0039] In some embodiments, the sintering is vacuum sintering, the heating rate is 2-6℃ / min, the sintering temperature is 1000-1300℃, and the sintering time is 5-30h.

[0040] In some embodiments, the method for modifying the nano-Si powder and the β-SiC powder with a silane coupling agent comprises: acid washing the nano-Si powder and the β-SiC powder with a low-concentration acid solution, washing with anhydrous ethanol in an inert atmosphere, and vacuum drying to obtain pretreated nano-Si powder and β-SiC powder; dispersing the pretreated nano-Si powder and the β-SiC powder in a silane hydrolysis solution, and reacting at 60-80℃ for 2-4h. After the reaction is completed, the product is washed with ethanol and dried.

[0041] Preferably, the nano-Si powder and the β-SiC powder are acid washed with hydrofluoric acid to remove the oxide layer on the surface of the nano-Si powder and the β-SiC powder.

[0042] In some embodiments, the mass ratio of the modified nano-Si powder to the modified β-SiC powder is 1:1-2, and the mass ratio of the sum of the two modified powders to the phenolic resin is 1:5-10, preferably 1:8-10.

[0043] In some embodiments, the method further comprises a step of repeatedly immersing the sintered ceramic piece in the impregnation liquid.

[0044] Preferably, the number of repeated immersions is 2-10, further preferably 3-8, until the mass change before and after sintering is less than 1%.

[0045] In a second aspect, the present application provides a 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic prepared by the preparation method.

[0046] In a third aspect, the present application provides an application of the 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic in the field of aerospace high-temperature components or electronic and power semiconductor heat dissipation / packaging.

[0047] The technical solutions of the present application are further described below in conjunction with embodiments, but the scope of protection of the present application is not limited thereto.

[0048] The raw materials used in the embodiments are all conventional raw materials, and the equipment used is all conventional equipment, and the products are commercially available.

[0049] Embodiment 1 A preparation method of a 3D-printed high-thermal-conductivity precursor-converted silicon carbide ceramic, which adopts the following specific step process: (1) Take silicon carbide powder, modified B4C nano powder and polycarbosilane powder, add the powders into toluene solvent, the mass percentage of silicon carbide powder in the slurry is 10 wt%, the mass percentage of modified B4C nano powder in the slurry is 1 wt%, and the mass ratio of polycarbosilane powder to organic solvent is 1:2, stir for 0.5 h under inert gas protection, and then put the slurry into a planetary ball mill for ball milling for 2 h; The preparation method of the modified B4C nano powder is as follows: add silane coupling agent into a mixed solution of 95 vol% dimethylbenzene and 5 vol% water, mix uniformly, then add B4C nano powder into the above solution, the mass ratio of B4C nano powder to silane coupling agent is 50:1, ultrasonic for 30 min, then continue to stir for 2 h, after the reaction is completed, wash with ethanol, and dry to obtain the product.

[0050] After ball milling, heat the slurry to 60℃ and stir to evaporate the organic solvent, and the solid content of the prepared 3D printing slurry is 75 wt%. The 3D printing slurry is extruded into a line shape, as shown in a and b in Figure 1 .

[0051] (2) Using the method of extrusion 3D printing, the printing rate is selected as 10 mm / min for layer-by-layer printing to obtain a silicon carbide blank. The blank is dried in a vacuum environment at 40°C for 12 h, and the dried blank is placed in a vacuum sintering furnace and heated to 100°C for 2 h, and then heated to 1100°C for 2 h to obtain a precursor converted silicon carbide ceramic.

[0052] (3) The obtained ceramic part is subjected to impregnation treatment: First, a phenolic resin solution is prepared: The preparation methods of the two modified nano powders are as follows: nano Si powder and β-SiC powder are respectively added to a 0.5wt% HF solution, stirred for 2 min, and after the reaction is completed, the powders are repeatedly rinsed with anhydrous ethanol to obtain pretreated nano Si powder and β-SiC powder, respectively; A modified solution is obtained by adding 2wt% silane coupling agent to a mixed solution of ethanol and deionized water in a volume ratio of 95:5; Then, the pretreated nano Si powder and β-SiC powder are added to the modified solution and reacted in the solution at 60°C for 2 h. After modification, the powders are washed with ethanol and then dried in a drying box.

[0053] Phenolic resin, modified nano Si powder and modified β-SiC powder are weighed. The mass ratio of modified nano Si powder to modified β-SiC powder is 1:1, the mass ratio of the total mass of the two modified nano powders to the mass of phenolic resin is 1:5, and the volume ratio of phenolic resin to ethanol is 1:2. The modified nano Si powder, modified β-SiC powder, phenolic resin and ethanol are mixed uniformly to obtain an impregnation solution. The precursor converted silicon carbide ceramic part is vacuum impregnated in the impregnation solution for 1 h.

[0054] (4) The impregnated precursor converted silicon carbide ceramic part is heated to 100°C in a vacuum sintering furnace for solidification, and then heated to 1500°C for sintering. The sintering time is 10 h to obtain a carbon / silicon carbide preform.

[0055] (5) The mass of the preform before and after sintering is recorded. When the weight change of the preform before and after sintering is less than 1% after 3 repeated impregnations, the impregnation process is completed.

[0056] (6) The preform is subjected to high-temperature molten silicon reaction in a high-temperature environment at 1700°C for 36 h to finally obtain a dense 3D printed high-thermal-conductivity precursor converted silicon carbide ceramic.

[0057] By Figure 2It is known that the flexural strength of silicon carbide ceramic parts after each impregnation was tested. The prepared silicon carbide ceramic samples were cut and ground to a size of 3mm × 4mm × 40mm, and the four edges were chamfered. The samples were placed in a three-point bending fixture and loaded at a constant stress rate at room temperature until fracture. The maximum load was recorded. At least six samples were tested in each group. The data were processed, and the average value and standard deviation were calculated. With the increase of the number of impregnations, the thermal conductivity of the ceramic parts gradually increased, which represents the increase in the density of the ceramic parts and the enhanced phonon transmission capacity inside the ceramic.

[0058] The fracture surface of the material was scanned using a SEM (Semiconductor Electron Microscope), such as... Figure 3 As shown in figures a and b, the impregnated material has a non-porous cross-section and high density. The density of the 3D-printed high thermal conductivity precursor converted to silicon carbide ceramic is 3.02 g / cm³. 3 It has a thermal conductivity of 136 W / (m·K) and a bending strength of 292 MPa.

[0059] Example 2 A method for preparing silicon carbide ceramics by converting a high thermal conductivity precursor for 3D printing, comprising the following specific steps: (1) Weigh out silicon carbide powder, modified B4C nanoparticles and polycarbosilane powder, add the powder to toluene solvent, the mass percentage of silicon carbide powder in the slurry is 10 wt%, the mass percentage of modified B4C nanoparticles in the slurry is 1 wt%, the mass ratio of polycarbosilane powder to organic solvent is 1:2, stir for 0.5 h under inert gas protection, and then put it into a planetary ball mill for ball milling for 2 h; Then, it is heated to 60°C and stirred. During stirring, the organic solvent evaporates, and the solid content of the prepared 3D printing slurry is 75wt%.

[0060] (2) Using extrusion 3D printing, the printing rate was selected as 10 mm / min for layer-by-layer stacking printing to obtain a silicon carbide complex structure blank. The blank was dried in a vacuum environment at 40 ℃ for 12 h. The dried blank was placed in a vacuum sintering furnace and heated to 100 ℃ for 2 h, and then heated to 1100 ℃ for 2 h to obtain the precursor converted silicon carbide ceramic.

[0061] (3) Impregnate the obtained ceramic parts: First, prepare a phenolic resin solution: Weigh out phenolic resin, modified nano-Si powder and modified β-SiC powder. The mass ratio of modified nano-Si powder to modified β-SiC powder is 1:1. The mass ratio of the sum of the two modified nano-powders to the mass of phenolic resin is 1:10. The volume ratio of phenolic resin to ethanol is 1:2. Mix the modified nano-Si powder, modified β-SiC powder, phenolic resin and ethanol evenly to obtain the impregnation solution. The precursor transformed silicon carbide ceramic part is vacuum impregnated in the impregnation liquid for 1 h.

[0062] (4) The impregnated precursor transformed silicon carbide ceramic part is heated to 100 ℃ for curing in a vacuum sintering furnace, and then heated to 1500 ℃ for sintering, with a sintering time of 10 h, to obtain a carbon / silicon carbide preform.

[0063] (5) The mass of the preform before and after sintering is recorded, and after repeating the impregnation for 3 times, when the weight change of the preform before and after sintering is less than 1%, the impregnation process is completed.

[0064] (6) The preform is subjected to high-temperature molten silicon reaction, and is kept at a high-temperature environment of 1700 ℃ for 30 h, to finally obtain a dense 3D printed high-thermal-conductivity precursor transformed silicon carbide ceramic.

[0065] The 3D printed high-thermal-conductivity precursor transformed silicon carbide ceramic has a density of 3.15 g / cm 3 , a thermal conductivity of 148 W / (m·K), and a bending strength of 315 MPa.

[0066] Example 3 A preparation method of a 3D printed high-thermal-conductivity precursor transformed silicon carbide ceramic, which comprises the following specific steps: (1) A silicon carbide powder, a modified B4C nano powder and a polycarbosilane powder are weighed, and the powders are added to a toluene solvent, with the silicon carbide powder accounting for 10 wt% of the slurry, the modified B4C nano powder accounting for 1 wt% of the slurry, and the mass ratio of the polycarbosilane powder to the organic solvent being 1:2. The mixture is stirred under inert gas protection for 0.5 h, and then is put into a planetary ball mill for ball milling for 2 h. Then the mixture is heated to 60 ℃ and stirred, and the organic solvent is evaporated during stirring. The solid content of the prepared 3D printing slurry is 75 wt%.

[0067] (2) An extrusion type 3D printing method is used, and the printing rate is selected to be 10 mm / min for layer-by-layer stacking printing, to obtain a silicon carbide complex structure blank.

[0068] The blank is dried in a vacuum environment at 40 ℃ for 12 h, and then is put into a vacuum sintering furnace and heated to 100 ℃ for 2 h, and then is continuously heated to 1100 ℃ for 2 h to obtain a precursor transformed silicon carbide ceramic.

[0069] (3) The obtained ceramic part is subjected to impregnation treatment: First, a phenolic resin solution is prepared: Take phenolic resin, modified nano-Si powder and modified beta-SiC powder, the mass ratio of modified nano-Si powder and modified beta-SiC powder is 1:2, the mass ratio of the sum of the two modified powders and phenolic resin is 1:8, the volume ratio of phenolic resin and ethanol is 1:2, mix the modified nano-Si powder and beta-SiC powder, phenolic resin and ethanol uniformly to obtain an impregnation solution; The precursor converted silicon carbide ceramic part is immersed in the impregnation solution in a vacuum environment for 1 h.

[0070] (4) The precursor converted silicon carbide ceramic part after impregnation is heated to 100 ℃ for solidification in a vacuum sintering furnace, and then heated to 1100 ℃ for sintering, and the sintering time is 10 h, to obtain a carbon / silicon carbide preform.

[0071] (5) The mass of the preform before and after sintering is recorded, and when the weight change of the preform before and after sintering is less than 1% after repeating the impregnation for 5 times, the impregnation process is completed.

[0072] (6) The preform is subjected to high-temperature molten silicon reaction, and is kept at a high-temperature environment of 1700 ℃ for 40 h, to finally obtain a dense 3D printed high-thermal-conductivity precursor converted silicon carbide ceramic.

[0073] Figure 4 The SEM scanning diagrams of the 3D printed silicon carbide ceramic after etching Si of the printed and impregnated twice (a) and four times (b) according to the present application are shown in Figs. Figure 4 As shown, with the increase of the number of impregnations, the second phase silicon carbide grains generated by reaction sintering become larger, and the material is more dense.

[0074] The 3D printed high-thermal-conductivity precursor converted silicon carbide ceramic has a density of 3.19 g / cm 3 , a thermal conductivity of 165 W / (m·K), and a bending strength of 329 MPa.

[0075] Comparative Example 1 The difference from Example 3 is that in step (3), the modified nano-Si powder and the modified beta-SiC powder are replaced by an equal amount of phenolic resin, and the rest is the same as Example 3.

[0076] The bending strength of the prepared silicon carbide ceramic part is 264 MPa, and the thermal conductivity is 124 W / (m·K).

[0077] Comparative Example 2 The difference from Example 3 is that in step (3), the modified nano-Si powder is replaced by an equal amount of modified beta-SiC powder, and the rest is the same as Example 3.

[0078] The bending strength of the prepared silicon carbide ceramic part is 284 MPa, and the thermal conductivity is 141 W / (m·K).

[0079] Comparative Example 3 The difference from Example 3 is that in step (3), the modified β-SiC powder is replaced by an equal amount of modified nano-Si powder, and the rest is the same as Example 3.

[0080] The bending strength of the prepared silicon carbide ceramic piece is 281 MPa, and the thermal conductivity is 135 W / (m·K).

[0081] Comparative Example 4 The difference from Example 3 is that the modified nano-Si powder and β-SiC powder are replaced by an equal amount of unmodified nano-Si powder and β-SiC powder, and the rest is the same as Example 1.

[0082] The bending strength of the prepared silicon carbide ceramic piece is 261 MPa, and the thermal conductivity is 119 W / (m·K).

[0083] Comparative Example 5 The difference from Example 3 is that the modified nano-Si powder is replaced by an equal amount of unmodified nano-Si powder, and the rest is the same as Example 1.

[0084] The bending strength of the prepared silicon carbide ceramic piece is 277 MPa, and the thermal conductivity is 132 W / (m·K).

[0085] Comparative Example 6 The difference from Example 3 is that in step (1), the silicon carbide is replaced by an equal amount of polycarbosilane powder, and the rest is the same as Example 3.

[0086] The bending strength of the prepared silicon carbide ceramic piece is 260 MPa, and the thermal conductivity is 129 W / (m·K).

[0087] Comparative Example 7 The difference from Example 3 is that in step (1), the modified B4C nano-powder is replaced by an equal amount of polycarbosilane powder, and the rest is the same as Example 3.

[0088] The bending strength of the prepared silicon carbide ceramic piece is 254 MPa, and the thermal conductivity is 129 W / (m·K).

[0089] Comparative Example 8 The difference from Example 3 is that in step (3), the two modified nano-powders are replaced by an equal amount of silane coupling agent modified nano-Si3N4 powder, and the rest is the same as Example 3.

[0090] The bending strength of the prepared silicon carbide ceramic piece is 302 MPa, and the thermal conductivity is 109 W / (m·K).

[0091] Comparative Example 9 The difference from example 3 is that in step (3), the mass ratio of the sum of the two modified nano-powders to the mass of the phenolic resin is 1:4, and the rest is the same as example 3.

[0092] The bending strength of the prepared silicon carbide ceramic piece is 258 MPa, and the thermal conductivity is 115 W / (m·K).

[0093] Comparative example 10 The difference from example 3 is that in step (3), the mass ratio of the sum of the two modified nano-powders to the mass of the phenolic resin is 1:13, and the rest is the same as example 3.

[0094] The bending strength of the prepared silicon carbide ceramic piece is 271 MPa, and the thermal conductivity is 124 W / (m·K).

[0095] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing silicon carbide ceramics by converting a high thermal conductivity precursor for 3D printing, characterized in that: Includes the following steps: Silicon carbide powder, silane coupling agent modified B4C nanoparticles, and polycarbosilane powder were added to an excess of aromatic hydrocarbons and / or chlorinated hydrocarbon organic solvents in a certain proportion. After being stirred evenly under an inert atmosphere, the mixture was placed in a planetary ball mill for ball milling. The rotation speed and time were set to ensure that the raw materials were mixed evenly to obtain a slurry. After adjusting the solid content of the slurry to the set value, a ceramic green body was prepared by 3D printing. The green body was dried and sintered to obtain a precursor-converted silicon carbide ceramic part. Silane coupling agent modified nano-Si powder and β-SiC powder were added to ethanol in a certain proportion with phenolic resin and mixed well to obtain impregnation solution. The precursor is converted into silicon carbide ceramic parts and vacuum impregnated in the impregnation liquid for 1-6 hours. After impregnation, the parts are first cured and then sintered at 1000-1700℃ to obtain the final product.

2. The method for preparing 3D printed high thermal conductivity precursor converted to silicon carbide ceramic according to claim 1, characterized in that: The aromatic hydrocarbon organic solvent is toluene or xylene; the chlorinated hydrocarbon organic solvent is chloroform or dichloromethane.

3. The method for preparing silicon carbide ceramics by converting a high thermal conductivity precursor for 3D printing according to claim 1, characterized in that: The mass ratio of polycarbosilane powder to organic solvent is 1:1-5; the mass percentage of silicon carbide powder in the slurry is 5-15%, and the mass percentage of modified B4C nanoparticles in the slurry is 0.5-3%.

4. The method for preparing 3D-printed high thermal conductivity precursor converted to silicon carbide ceramic according to claim 1, characterized in that: The stirring time under an inert atmosphere is 0.5-2 hours. After stirring, the slurry is heated to evaporate the organic solvent in the slurry and adjust the solid content in the slurry to 65-95%.

5. The method for preparing silicon carbide ceramics by converting a high thermal conductivity precursor for 3D printing according to claim 1, characterized in that: The green body is dried under vacuum for 5-24 hours at a temperature of less than 50℃.

6. The method for preparing 3D-printed high thermal conductivity precursor converted to silicon carbide ceramic according to claim 1, characterized in that: The sintering is vacuum sintering, with a heating rate of 2-6℃ / min, a sintering temperature of 1000-1300℃, and a sintering time of 5-30h.

7. The method for preparing 3D-printed high thermal conductivity precursor converted to silicon carbide ceramic according to claim 1, characterized in that: The method for modifying nano-Si powder and / or nano-β-SiC powder with silane coupling agent is as follows: after acid washing and drying, nano-Si powder and / or nano-β-SiC powder are obtained as pretreated nano-β-SiC powder. Pretreated nano-Si powder and / or nano-β-SiC powder are dispersed in silane hydrolysate and reacted at 60-80℃ for 2-4 hours. After the reaction is complete, the powder is washed with ethanol and dried to obtain the final product.

8. The method for preparing 3D-printed high thermal conductivity precursor converted to silicon carbide ceramic according to claim 1, characterized in that: In the impregnation solution, the mass ratio of modified nano-Si powder to β-SiC powder is 1:1-2, and the mass ratio of the sum of the masses of nano-Si powder and nano-β-SiC powder modified by silane coupling agent to the mass ratio of phenolic resin is 1:5-10.

9. A 3D-printed high thermal conductivity precursor for converting silicon carbide ceramics, characterized in that: It is prepared by any one of the preparation methods described in claims 1-8.

10. The application of the 3D-printed high thermal conductivity precursor of claim 9 to silicon carbide ceramics in the fields of aerospace high-temperature components or electronic and power semiconductor heat dissipation / packaging.